2014
DOI: 10.3109/09513590.2014.946899
|View full text |Cite
|
Sign up to set email alerts
|

Selected CNR1 polymorphisms and hyperandrogenemia as well as fat mass and fat distribution in women with polycystic ovary syndrome

Abstract: The endocannabinoid system is postulated to play an important role in the etiology of obesity, insulin resistance, fat distribution and metabolic disorders. Insulin resistance associated with abdominal obesity plays a leading role in the etiology of hyperandrogenism and other clinical features of the polycystic ovary syndrome (PCOS). A total of 174 women 16-38 years old, diagnosed with PCOS according to the Rotterdam criteria are recruited. Control group consisted of 125 healthy women 18-45 years old. Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…None of the women from the study population were on an elimination diet, suffered from chronic or systemic illness, or used lipid-and glucose-lowering drugs or oral contraceptive pills. This group was precisely described previously [9].…”
Section: Study Groupmentioning
confidence: 99%
“…None of the women from the study population were on an elimination diet, suffered from chronic or systemic illness, or used lipid-and glucose-lowering drugs or oral contraceptive pills. This group was precisely described previously [9].…”
Section: Study Groupmentioning
confidence: 99%
“…Recent studies revealed that overactivation of the endocannabinoid system is linked to insulin resistance and the progression of PCOS [ 84 , 85 ]. It has also been reported that genetic polymorphism of cannabinoids receptor 1 influences the hyperandrogenemia state in PCOS women and the development of NAFLD [ 86 , 87 ]. Antagonism of cannabinoids receptor 1 leads to the improvement of hepatic steatosis and insulin resistance [ 88 ].…”
Section: The Potential Molecular Link Between Nafld and Pcosmentioning
confidence: 99%
“…Weight loss even by 5 % improves insulin sensitivity, concentration of SHBG, lowers testosterone level and can bring about normalization of menstrual cycle disorders, spontaneous ovulations and higher percentage of ovulations. Thus, while treating women with PCOS and without obesity, all efforts should be directed at obesity prevention [12].…”
Section: Changing a Lifestyle With Following A Healthy Dietmentioning
confidence: 99%